To selection of technological scheme of softening heat treatment for high chromium cast iron - Efremenko, V. G.; Chabak, YU. G.; Shimizy, K.; Dzherenova, A. V.; Efremenko, B. V. (Science and Transport Progress, 2014)
Purpose. High chromium cast irons with austenitic matrix have low machinability. The aim of work is search of new energy-saving modes of preliminary softening heat treatment enhancing the machinability of castings by forming an optimum microstructure. Methodology. Metallographic analysis, hardness testing and machinability testing are applied. Findings. It was found out that high temperature annealing with continuous cooling yields to martensite-austenite matrix in cast iron 270Х15Г2Н1MPhT, which abruptly affects the machinability of cast iron. Significant improvement of machinability is achieved by forming of structure "ferrite + granular carbides" and by decline of hardness to 37-39 HRC in the case of two-stage isothermal annealing in the subcritical temperature range or by the use of quenching and tempering (two-step or cyclic). Originality. It was found that the formation of the optimal structure of the matrix and achievement of desired hardness level needed for improving machinability of high chromium cast iron containing 3 % austenite-forming elements, can be obtained: 1) due to pearlite original austenite followed by spherodization eutectoid carbides, and 2) by getting predominantly martensite structure followed by the decay of martensite and carbides coagulation at high-temperature tempering. Practical value. The new energy-saving schemes of softening heat treatment to ensure the growth of machinability of high chromium cast iron, alloyed by higher quantity of austenite forming elements, are proposed.